Formulasi Dan Karakterisasi Kue Kering yang Difortifikasi Abon Ikan Cakalang Asap - Malawo, Melanti; Naiu, Asri Silvana; Dali, Faiza A (The NIKe Journal, 2024)
This research aims to determine the results of fortification of smoked skipjack tuna (Katsuwonus pelamis, L) floss on hedonic and chemical values, as well as the hedonic quality of selected dry cakes. This research consisted of 3 stages, namely making fish floss, formulating dry cakes fortified with smoked skipjack tuna floss and characterization of smoked skipjack tuna floss dry cakes. The treatment in this research was fortification of smoked skipjack tuna floss with concentrations of 10%, 20% and 30%. Data analysis used for hedonic organoleptic testing was Kruskal Wallis followed by Duncan's advanced test, and for proximate testing using Anova followed by Duncan's advanced test. Determination of selected products is carried out using the Bayes test. The results showed that the fortification of smoked skipjack tuna floss had a real influence on taste, aroma, texture, appearance, color, protein content, water content and carbohydrate content, but did not have a real effect on fat content and ash content. Dry cakes fortified with smoked skipjack tuna floss with a concentration of 20% are the selected products, with protein content of 10.86%, water 8.71%, fat 28.87%, carbohydrates 50.02% and ash 1.52%. In terms of organoleptic hedonic quality, the selected product has a score of 8 for all parameters, which means it has a complete, neat, homogeneous, reddish yellow appearance, has a delicious taste, the taste of smoked skipjack tuna is very strong, tastes sweet and savory, the texture is crunchy, compact, dense , the specific aroma of smoked skipjack tuna floss is quite strong, and has a reddish brown color.